Prevalence, management, and outcomes of patients with coagulopathy after acute nonvariceal upper gastrointestinal bleeding in the United Kingdom. - Jairath, V; Kahan, B; Stanworth, S; Logan, R; Hearnshaw, SA; Travis, S; Palmer, K; Murphy, M (2013)
BACKGROUND: Coagulopathy after major hemorrhage has been found to be an independent risk factor for mortality after traumatic bleeding. It is unclear whether similar associations are present in other causes of major hemorrhage. We describe the prevalence, use of plasma, and outcomes of patients with coagulopathy after acute nonvariceal upper gastrointestinal bleeding (NVUGIB). STUDY DESIGN AND METHODS: This study was a multicenter UK national audit. Data were collected prospectively on consecutive admissions with upper gastrointestinal bleeding over a 2-month period to 212 UK hospitals. Coagulopathy was defined as an international normalized ratio (INR) of at least 1.5. Logistic regression was used to examine the relationship between coagulopathy and patient-related outcome measures of mortality, rebleeding, and need for surgery and/or radiologic intervention. RESULTS: A total of 4478 patients were included in the study. Coagulopathy was present in 16.4% (444/2709) of patients in whom an INR was recorded. Patients with coagulopathy were more likely to present with hemodynamic shock (45% vs. 36%), have a higher clinical Rockall score (4 vs. 2), receive red blood cell transfusion (79% vs. 48%) and have high-risk stigmata of hemorrhage at endoscopy (34% vs. 25%). After adjustment for confounders the presence of a coagulopathy was associated with a fivefold increased in the odds of mortality (odds ratio, 5.63; 95% confidence interval, 3.09-10.27; p < 0.001). Only 35% of patients with coagulopathy received fresh-frozen plasma transfusion. CONCLUSIONS: Coagulopathy was prevalent in 16% of patients after NVUGIB and independently associated with more than a fivefold increase in the odds of in-hospital mortality. Wide variation in plasma use exists indicates clinical uncertainty regarding optimal practice.